2019
DOI: 10.1021/acs.joc.9b00075
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Nickel Catalyzed C–S Cross-Coupling under Mild Conditions Using Metal–Ligand Cooperativity

Abstract: A simple and efficient approach of C–S cross-coupling of a wide variety of (hetero)­aryl thiols and (hetero)­aryl halides under mild conditions, mostly at room temperature, catalyzed by well-defined singlet diradical Ni­(II) catalysts bearing redox noninnocent ligands is reported. Taking advantage of ligand centered redox events, the high-energetic Ni(0)/Ni­(II) or Ni­(I)/Ni­(III) redox steps were avoided in the catalytic cycle. The cooperative participation of both nickel and the coordinated ligands during ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 83 publications
3
48
0
Order By: Relevance
“…Recently, we reported CÀ S cross-coupling reactions of a broad range of aryl halides and thiols under mild reaction conditions catalyzed by singlet di-radical nickel(II)-complexes [Ni II {(L 1À 3 ) *À } 2 ] (1-3) featuring redox-active diamine based ligands (Scheme 1). [16,17] In this work we demonstrated that the energetically demanding nickel-centered redox processes can be averted via cooperative involvement of both nickel and ligand-centered redox processes during catalytic turnover even in absence of the expensive photosensitizers. DFT studies indicated that during oxidative addition (of aryl halides) and reductive elimination nickel and one of the di-amine ligands in catalyst 3 undergo single electron oxidation and reduction respectively, and thus avoid the energetically unfavorable nickel(II)/nickel(IV) (during oxidative addition) and nickel(II)/nickel(0) (during reductive elimination) oxidation states.…”
Section: Full Papermentioning
confidence: 79%
See 3 more Smart Citations
“…Recently, we reported CÀ S cross-coupling reactions of a broad range of aryl halides and thiols under mild reaction conditions catalyzed by singlet di-radical nickel(II)-complexes [Ni II {(L 1À 3 ) *À } 2 ] (1-3) featuring redox-active diamine based ligands (Scheme 1). [16,17] In this work we demonstrated that the energetically demanding nickel-centered redox processes can be averted via cooperative involvement of both nickel and ligand-centered redox processes during catalytic turnover even in absence of the expensive photosensitizers. DFT studies indicated that during oxidative addition (of aryl halides) and reductive elimination nickel and one of the di-amine ligands in catalyst 3 undergo single electron oxidation and reduction respectively, and thus avoid the energetically unfavorable nickel(II)/nickel(IV) (during oxidative addition) and nickel(II)/nickel(0) (during reductive elimination) oxidation states.…”
Section: Full Papermentioning
confidence: 79%
“…[2] To obtain the optimal reaction parameters for the N-arylation reactions, we studied the reaction of 1H-pyrazole (4 a) and iodobenzene (5 a) under different reaction conditions using the nickel(II)complexes, [Ni II {(L 1 ) *À } 2 ](1), [Ni II {(L 2 ) *À } 2 ](2), and [Ni II {(L 3 ) *À } 2 ](3) as catalysts ( Table 1). [16,17] Optimiza- (3) as the catalyst revealed that the highest yield (82%) of 1-phenyl-1H-pyrazole (6 a) was obtained when the reaction was carried out in an CH 3 CN/DMF (5:1) solvent mixture at room temperature in presence of 8.0 mol% of the catalyst 3 and 1.40 equiv. of NaO t Bu as base (Table 1, entry 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For catalyst 1 a inert condition and slightly higher temperature is required to get the products in satisfactory yields while the catalyst 2 a affords the respective pyrimidines in even higher yields under comparatively mild aerobic conditions. Moreover, the metal‐ligand cooperativity and active involvement of ligand centered radical in 2 a allow to achieve pyrimidines in good yields even starting from unactivated alcohols bearing strongly electron‐withdrawing substituents. Overall, the metal‐ligand cooperative approach via active involvement of the ligand centered redox process during catalysis allow to avoid the energetically demanding high energy nickel centered redox processes and allow to achieve the reactions under mild and aerobic conditions.…”
Section: Resultsmentioning
confidence: 99%